#### Question

Find cube root of \sqrt[3]{45+29\sqrt{2}}

Question

Find cube root of \sqrt[3]{45+29\sqrt{2}}

Let

45+29\sqrt{2} = (a+b\sqrt{2})^3

45-29\sqrt{2} = (a-b\sqrt{2})^3

in which a and b are positive integers

Addition of the two equations gives

(a+b\sqrt{2})^3+(a-b\sqrt{2})^3 = 90

Factoring the LHS using sum of cubes formula.

2a[(a+b\sqrt{2})^2+(a-b\sqrt{2})^2-a^2+2b^2)=90

a(2a^2+2b^2\cdot 2 - a^2+2b^2) = 45

a^3 + 6ab^2 = 45

(1)

Multiplying the two equations gives

(45+29\sqrt{2})(45-29\sqrt{2}) = (a+b\sqrt{2})^3 (a-b\sqrt{2})^3

Simplify the equation using difference of square formula

(a^2 - b^2\cdot 2)^3 = 45^2 - 29^2\cdot 2=343

Taking cube root gives

a^2-2b^2 = 7

(2)

A system of equations is obtained from (1) and (2)

\begin{cases} a^3 + 6ab^2 &=45 \\ a^2-2b^2 &=7 \end{cases}

Solving the equation yields

a = 3, b=1

Therefore,

The cube root of

\sqrt[3]{45+29\sqrt{2}}=\sqrt[3]{(3+\sqrt{2})^3}=3+\sqrt{2}

\sqrt[3]{45-29\sqrt{2}}=\sqrt[3]{(3-\sqrt{2})^3}=3-\sqrt{2}